Physico-chemical properties of cationic niosomes loaded with fraction of rice (Oryza sativa) bran extract - Manosroi A. (2014)
The aim of this study was to investigate the physico-chemical properties of cationic niosomes (Tween61/cholesterol/CTAB) loaded with fraction No. 3 of Oryza sativa bran extract (OSF3) at 0.1, 0.5, 1.0 and 2.0% (w/v), respectively, before and after ultra-centrifugation. More white milky translucent appearance of the niosomes was observed at the higher loaded amount of OSF3. The entrapment efficiency of 0.5% OSF3 in niosomes was 86.22plusmn;1-43%. The sizes of the niosomes were slightly increased (120-220 nm) and the zeta potential values were decreased from 80 to the range of 40-60 mV after loaded with OSF3. All niosomes both blank and loaded with OSF3 were in the uni-lamellar structures determined by FF-TEM and SAXS. The transitions temperature (T c) of niosomes significant increased from 75 to 80 °C when loaded with OSF3 at 0.1 and 0.5%. Moreover, blank niosomes showed the highest microviscosity with the most rigid membrane at 25 °C, followed by the niosomes loaded with 0.1, 0.5, 1.0 and 2.0% of OSF3, respectively. The fluorescence polarizations of all niosomal formulations indicated the sharp descending phases at about 40 and 70 °C. After ultra-centrifugation to eliminate the non-loaded negatively charged OSF3, the increased vesicular sizes and zeta potential values of the blank, loaded niosomes with 0.1 and 0.5% OSF3 were observed. All niosomal formulations gave the same transition temperatures at about 71 °C and the same microviscosities at 25 °C. The results from this study can be applied for the niosomal formulation development of the rice bran semi-purified fraction for anti-hair loss products. Copyright © 2012 American Scientific Publishers All rights reserved.